2015
DOI: 10.1161/circresaha.116.305547
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of Gata4, Mef2c, and Tbx5 Influences the Efficiency and Quality of Induced Cardiac Myocyte Reprogramming

Abstract: Rationale Generation of induced cardiac myocytes (iCMs) directly from fibroblasts offers great opportunities for cardiac disease modeling and cardiac regeneration. A major challenge of iCM generation is the low conversion rate of fibroblasts to fully reprogrammed iCMs, which could in part be attributed to unbalanced expression of reprogramming factors Gata4 (G), Mef2c (M), and Tbx5 (T) using the current gene delivery approach. Objective We aimed to establish a system to express distinct ratios of G, M, T pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
227
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(239 citation statements)
references
References 38 publications
11
227
0
1
Order By: Relevance
“…13 In this study, Wang et al generated 6 polycistronic constructs with identical self-cleaving 2A peptides (P2A and T2A) to include all possible splicing orders of G, M, and T in a single transgene (ie, MGT, MTG, GMT, GTM, TMG, and TGM; Figure). 15 The total and endogenous transcript levels of G, M, and T were not significantly different in the CFs transduced with the 6 polycistronic vectors, whereas the G, M, and T protein expression was high when the reprogramming factor was placed at the 5′ end of a polycistronic construct, upstream of the P2A peptide. This is consistent with the results of a previous study demonstrating that the P2A peptide is more efficiently cleaved than other 2A peptides for efficient protein translation from polycistronic vectors.…”
Section: Article See P 237mentioning
confidence: 90%
See 1 more Smart Citation
“…13 In this study, Wang et al generated 6 polycistronic constructs with identical self-cleaving 2A peptides (P2A and T2A) to include all possible splicing orders of G, M, and T in a single transgene (ie, MGT, MTG, GMT, GTM, TMG, and TGM; Figure). 15 The total and endogenous transcript levels of G, M, and T were not significantly different in the CFs transduced with the 6 polycistronic vectors, whereas the G, M, and T protein expression was high when the reprogramming factor was placed at the 5′ end of a polycistronic construct, upstream of the P2A peptide. This is consistent with the results of a previous study demonstrating that the P2A peptide is more efficiently cleaved than other 2A peptides for efficient protein translation from polycistronic vectors.…”
Section: Article See P 237mentioning
confidence: 90%
“…In this issue, Wang et al 15 generated a complete set of polycistronic constructs encoding G, M, and T with all possible splicing orders and analyzed the cardiac reprogramming efficiency using these vectors. They found that each polycistronic vector gave rise to distinct G, M, and T protein expression levels, and that an optimal balance of G, M, and T protein expression greatly improved both the efficiency and the quality of cardiac reprogramming.…”
mentioning
confidence: 99%
“…29 The low and variable reprogramming efficiency by GMT may be because of the stoichiometry of reprogramming factors in the cells transduced with separate vectors. 80,82 To address this, Wang et al 83 recently generated all possible polycistronic vectors of GMT and demonstrated that the stoichiometry of reprogramming factors is indeed critical for cardiac reprogramming. They found that the 2 polycistronic vectors, MGT and MTG, which expressed a high level of Mef2c and low levels of Gata4 and Tbx5, enhanced cardiac reprogramming, whereas the other vectors reduced reprogramming efficiency (Figure 2).…”
Section: Circulation Researchmentioning
confidence: 99%
“…The reprogramming efficiency of the retrovirus-mediated gene delivery approach is partially dependent on the stoichiometry of the delivered transcription factors [102]. It was reported that a higher reprogramming efficiency than that achieved in the original GMT experiment when the stoichiometry of the transcription factors is altered [102]. In this investigation, six different polycistronic lentiviral vectors were constructed to cover all possible combinations of G, M, T with identical internal 2A sequences.…”
Section: Gene Delivery Of Reprogramming Factors Via Retroviral Vectorsmentioning
confidence: 97%
“…This method has been used by several groups and the efficiency of reprogramming has been enhanced by using alternative transcription factors or small molecules (summarized in Tables 2 and 3). The reprogramming efficiency of the retrovirus-mediated gene delivery approach is partially dependent on the stoichiometry of the delivered transcription factors [102]. It was reported that a higher reprogramming efficiency than that achieved in the original GMT experiment when the stoichiometry of the transcription factors is altered [102].…”
Section: Gene Delivery Of Reprogramming Factors Via Retroviral Vectorsmentioning
confidence: 99%